On the Solution of MHD Jeffery–Hamel Flow by Weighted Residual Method - Alao, S.; Akinola, E.I.; Salaudeen, K.A.; Oderinu, R.A.; Akinpelu, F.O. (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2017)
This article presents the numerical solution of MHD Hamel-Jeffery flow using weighted residual method under which two cases of trial function is examined. The effect of Hartmann and Reynolds number was discussed. Comparisons were made with the exact solution to check the efficiency and accuracy of the method. The results reveal that the method is very effective and simple in solving nonlinear problems. The results obtained are in polynomial form that makes it possible to evaluate the solution at any point in the region.